“Always being there for each other”: adolescent girls’ experiences of their same-sex friendships in a Western Cape boarding school - Truter, Zelda Marthani (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.